Evaluating the fermentation characteristics, bacterial community, and predicted functional profiles of native grass ensiled with different additives - Du, Shuai; You, Sihan; Jiang, Xiaowei; Li, Yuyu; Wang, Ruifeng; Ge, Gentu; Jia, Yushan (Frontiers in Microbiology, 2022)
Bioaugmentation of native grass ensiling with Lactobacillus plantarum or Lactobacillus buchneri or Pediococcus pentosaceus on the ensiling performance and bacterial community was investigated after 30 days of the fermentation process. The native grass was inoculated with distilled water, Lactobacillus plantarum, Lactobacillus plantarum, and Lactobacillus buchneri, and Lactobacillus plantarum, Lactobacillus buchneri, and Pediococcus pentosaceus as the CON treatment, T1 treatment, T2 treatment, and T3 treatment, respectively. The addition of lactic acid bacteria was added at a total of 1 × 106 colony-forming unit/g of fresh weight. As expected, the markedly (p < 0.05) lower water-soluble carbohydrate content was tested in the T2 and T3 treatments compared to the CON and T1 treatments. Compared to the CON and T1 treatment, significantly (p < 0.05) higher crude protein content, and lower acid detergent fiber and neutral detergent fiber contents were found in the T2 and T3 treatments. Compared to the CON treatment, the pH significantly (p < 0.05) decreased in the lactic acid bacteria (LAB) inoculated silage, and the lowest pH was measured in the T3 treatment. Similarly, significantly higher lactic acid and acetic acid contents were also found in the T3 treatment compared to those in other treatments. After 30 days of ensiling, the Shannon and Chao1 indexes in silages decreased compared to that in the fresh materials (FMs). The principal coordinate analysis indicated that both FM and silage were distinctly separated in each treatment with no interactions on the confidence ellipse (R = 0.8933, p = 0.001). At the phylum level, the dominant phylum was shifted from Proteobacteria to Firmicutes after the fermentation process. Interestingly, Weissella dominated the fermentation in the CON treatment and Lactobacillus dominated the fermentation in all inoculated LAB silages at the genus level. Results of functional prediction analyses showed that the metabolism of amino acid, cofactors, and vitamins, and membrane transport was reduced, while the metabolism of nucleotide and majority carbohydrates was increased after ensiling. The complex LAB (Lactobacillus plantarum, Lactobacillus buchneri, and Pediococcus pentosaceus) exhibited the potential possibility to decrease pH and enhance the relative abundance of LAB in response to obtaining high-quality silage by the synergistic effects. These results suggested that the complex LAB could improve the ensiling performance of native grass silage, and lay a theoretical basis for inoculant application in native grass.